SIMULASI SISTEM PENDETEKSI UNTUK PERALATAN ELEKTRONIK DI RUMAH MELALUI SMS( Short Messages Service ) - Laxsmy Devy (Elektron : Jurnal Ilmiah, 2009)
Simulation of detection system for equipments electronics aim to facilitate people watch existence of equipments electronics or other valuable objects that still residing in on position which determined, if house in a state of remained house owner. This detection also at the same time can be functioned as preventative of thief. This detection system use 2 of HP ( Handphone), HP1 reside in house which incircuit with detection system and HP2 holded by house owner. Existence of electronics equipments that residing in house can be watched automatically from long distance with delivering SMS from HP1 to HP2 on the happening of condition of electronic equipments making of move from initialy position, also alarm will sound at home for notification to security or neighbour. SMS can be also delivered from HP2 to HP1 for the checking of electronic equipments if notification of HP2 at home don’t be executed when position the electronic equipments have making a move. The detection in the form of censor infra red (optocoupler) residing in at elbow equipments of electronic at home which input to parallel port ( DB25) of PC ( personal of computer). While HP1 incircuit serially port ( DB9) and thsi function of HP is executed by program of Visual Basic 6.0. Program to detect infra red and activate alarm also use Visually Basic 6.0.